Inventarisasi Jenis dan Keberadaan Serpentes di Taman Hutan Raya Ir. H. Djuanda Jawa Barat - Srimulyaningsih, Reni; Mardiana, Bima (Universitas Pattimura, 2025)
Snakes have an important role in the ecosystem as predators controlling prey populations and as prey for predators. They are found in habitats such as tropical rainforests, savannas, and mountainous areas. The research object is to inventory and identify the potential of snake species in Taman Hutan Raya Ir. H. Djuanda. The method of research by VES (a Visual Encounter Survey) was then analyzed by description. There were found Four snake species in the Tahura Ir. H. Djuanda, namely, red triangle snake (Xenochrophis trianguligerus) with a frequency of 3 encounters on the ground near the water source, shoot snake (Ahaetulla prasina) with a frequency of 1 encounter in the bushes, koros snake (Ptyas korros) with a frequency of 1 encounter in the bushes near the water source, and coffee snake (Coelognathus flavolineatus) with a frequency of 1 encounter in jogging track area. The distribution of snake species in the Ir. H. Djuanda Grand Forest Park area is spread across two management blocks: protection and utilization blocks.